1992
DOI: 10.1017/s0022112092001472
|View full text |Cite
|
Sign up to set email alerts
|

A numerical study of vortex shedding from flat plates with square leading and trailing edges

Abstract: This paper describes a numerical study of the flow around flat plates with square leading and trailing edges on the basis of a finite-difference analysis of the two-dimensional Navier—Stokes equations. The chord-to-thickness ratio of a plate, d/h, ranges from 3 to 9 and the value of the Reynolds number based on the plate's thickness is constant and equal to 103. The numerical computation confirms the finding obtained in our previous experiments that vortex shedding from flat plates with square leading and trai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
43
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 2 publications
6
43
0
Order By: Relevance
“…One thing common to all the above methods is that their results are meaningful only when a su$cient spatial resolution is employed; therefore, these methods are memory intensive and require a lot of processing time. Ohya et al (1992) demonstrated that using a 2-D analysis it was possible to simulate the discontinuity of Strouhal number for 6)06B/D68)0 at Re"10. Nozu & Tamura (1997) pointed out the variation of #ow mechanisms around a square cylinder using 3-D computation, showing that 3-D structures begin to appear already as early as Re"2;10, and clusters of small-scale eddies which are a manifestation of three-dimensionality exist in the vortex structure of the wake at Re"10.…”
Section: Introductionmentioning
confidence: 99%
“…One thing common to all the above methods is that their results are meaningful only when a su$cient spatial resolution is employed; therefore, these methods are memory intensive and require a lot of processing time. Ohya et al (1992) demonstrated that using a 2-D analysis it was possible to simulate the discontinuity of Strouhal number for 6)06B/D68)0 at Re"10. Nozu & Tamura (1997) pointed out the variation of #ow mechanisms around a square cylinder using 3-D computation, showing that 3-D structures begin to appear already as early as Re"2;10, and clusters of small-scale eddies which are a manifestation of three-dimensionality exist in the vortex structure of the wake at Re"10.…”
Section: Introductionmentioning
confidence: 99%
“…The #ow around rectangular plates in the absence of any external forcing has been studied previously both experimentally and numerically (Nakamura et al 1991;Ohya et al 1992). The vortex shedding from the leading edge of the plate generally locked to a single frequency at low Reynolds numbers [up to Re&3000, Nakamura et al (1991)].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of Ohya et al (1992) where it was observed, the trailing-edge shedding was not considered to be part of the feedback loop but merely led to contamination of the downstream wake. The present study approaches the problem of natural shedding modes from a di!erent perspective in order to establish the importance of trailing-edge shedding to the self-sustained oscillations.…”
Section: Introductionmentioning
confidence: 99%
“…However, elongating the plate in the streamwise direction weakens the interaction and introduces considerable complexity into the features of the separated shear layers, which are highly related to those of the impinging shear layer and the vortices that are shed from the leading edge. The characteristics of the shedding vortices superimposed in the separated shear layer above the plate play a significant role in flow-induced structural vibration and acoustics (Ohya et al, 1992). Understanding the characteristics of vortex shedding from an elongated blunt body and the influence of vortex shedding on the separated shear layer is highly desirable.…”
Section: Introductionmentioning
confidence: 99%